Showoff - Korman, Gordon (New York : Scholastic Inc., 2012)
Accused of ruining a champion dog's career after an unfortunate incident at a mall show, Luthor is sent to the pound, prompting a skeptical Griffin to hatch a daring plan involving a sinister saboteur, a reclusive trainer, and large supply of red dye.
M
b
b
Keywords: Show dogs -- Juvenile fiction; Undercover operations -- Juvenile fiction; Show dogs -- Fiction; Undercover operations -- Fiction; Adventure and adventurers -- Fiction; Adventure stories